2004
DOI: 10.1093/toxsci/kfi027
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Nrf2 by tBHQ Confers Protection against Oxidative Stress-Induced Cell Death in Human Neural Stem Cells

Abstract: Recent studies indicate that NF-E2 related factor 2 (Nrf2) is a substrate for the ubiquitin-proteasome pathway. The present study is aimed to determine whether increased protein stability is a mechanism by which quinone compounds, like tert-butylhydroquinone (tBHQ), may enhance Nrf2-mediated transcriptional activation and subsequent antioxidant protection. H2O2-induced necrotic cell death, evidenced by transmission electronic microscope (TEM) imaging with no caspase 3 activation and PARP cleavage, was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
153
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 37 publications
13
153
0
1
Order By: Relevance
“…Its oral formulation BG-12 has been recently approved for the treatment of multiple sclerosis (Linker et al, 2011). Other molecules able to stabilize Nrf2 are the quinone compound tert-butylhydroquinone (tBHQ) (Li et al, 2005) and the triterpenoids bardoxolone methyl (Dinkova-Kostova et al, 2005) and RTA 408 (Probst et al, 2015), both of which are currently in clinical trials.…”
Section: Nrf2 Activatorsmentioning
confidence: 99%
“…Its oral formulation BG-12 has been recently approved for the treatment of multiple sclerosis (Linker et al, 2011). Other molecules able to stabilize Nrf2 are the quinone compound tert-butylhydroquinone (tBHQ) (Li et al, 2005) and the triterpenoids bardoxolone methyl (Dinkova-Kostova et al, 2005) and RTA 408 (Probst et al, 2015), both of which are currently in clinical trials.…”
Section: Nrf2 Activatorsmentioning
confidence: 99%
“…Activation of Nrf2 and Nrf2-mediated antioxidant enzyme gene expression by pro-oxidants, including H 2 O 2 at moderate non-lethal doses suggests that Nrf2 signaling may control the adaptive response of neuronal cells to oxidative insults. 29 This potential Nrf2-mediated adaptive response to oxidative stress is particularly relevant to SCI where the increased level of ROS is constantly generated for a prolonged period of time leading to progressive oxidative stress in secondary injury of SCI. 18 Systematic increases in Nrf2 and ARE-driven heme oxygenase-1 in the spinal cord of SOD G93A rats, an experimental model of ALS, have been reported, 30,31 which may represent an adaptive response to oxidative stress.…”
Section: Ros and Oxidative Stress In Scimentioning
confidence: 99%
“…Studies have suggested that the protective role of these compounds against oxidative stress damage is mediated, at least partially, by effects on signaling molecules including extracellular signal-regulated kinase, nuclear factor kB and Nrf2. 18,[27][28][29][30][31] Nrf2 signaling appears to has a central role in regulating the induction of antioxidants by phenolic compounds. 18,[27][28][29][30][31] …”
Section: Nucleusmentioning
confidence: 99%
“…31,33,34 Recent studies have demonstrated that BG00012 and monomethyl fumarate can activate Nrf2 in vitro. 35 The Nrf2 pathway has been implicated as a mediator of a range of neuroprotective effects in the CNS, including inhibition of oxidative and excitotoxic neuronal damage, [36][37][38][39][40] protection of the BBB 41 and regulation of myelin maintenance. 42 Hence, the current body of experimental evidence suggests that BG00012 may provide a dual neuroprotective and anti-inflammatory a report by therapeutic effect not targeted by contemporary MS therapies (see Figure 2).…”
mentioning
confidence: 99%